2017
DOI: 10.3899/jrheum.161539
|View full text |Cite
|
Sign up to set email alerts
|

Two-year Efficacy and Safety of Subcutaneous Tocilizumab in Combination with Disease-modifying Antirheumatic Drugs Including Escalation to Weekly Dosing in Rheumatoid Arthritis

Abstract: Objective.To evaluate the longterm efficacy and safety of subcutaneous tocilizumab (TCZ-SC) every 2 weeks (q2w) over 2 years in patients with rheumatoid arthritis who have an inadequate response to disease-modifying antirheumatic drugs (DMARD).Methods.Patients (n = 656) were randomized 2:1 to TCZ-SC 162 mg q2w or placebo-SC q2w plus DMARD. After a 24-week double-blind period, patients (n = 457) were rerandomized to open-label TCZ-SC q2w by means of prefilled syringe or autoinjector. Escape therapy with weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The intravenous and SC formulations of tocilizumab have been shown to be safe and effective treatments for patients with RA who are bDMARD naïve and for those with prior exposure to bDMARDs, either as a monotherapy or in combination with csDMARDs [21][22][23][24][25]. As shown in the present study, patients (particularly those treated with tocilizumab) may receive third, fourth, or greater lines of biologic therapy.…”
Section: Fig 2 Lines Of Bdmard Therapy By Biologicmentioning
confidence: 93%
See 1 more Smart Citation
“…The intravenous and SC formulations of tocilizumab have been shown to be safe and effective treatments for patients with RA who are bDMARD naïve and for those with prior exposure to bDMARDs, either as a monotherapy or in combination with csDMARDs [21][22][23][24][25]. As shown in the present study, patients (particularly those treated with tocilizumab) may receive third, fourth, or greater lines of biologic therapy.…”
Section: Fig 2 Lines Of Bdmard Therapy By Biologicmentioning
confidence: 93%
“…3 Adjusted mean primary persistence with bDMARDs among patients with RA a Fig. 4 Adjusted mean secondary persistence with bDMARDs among patients with RA a Reference bDMARD biologic disease-modifying antirheumatic drug a Hazard ratios were derived from the survival models after adjusting for patients' baseline demographics, lines of therapy, and episode-specific comorbidities Reference bDMARD biologic disease-modifying antirheumatic drug a Hazard ratios were derived from the survival models after adjusting for patients' baseline demographics, lines of therapy, and episode-specific comorbidities improvements in ACR response and DAS28 remission were achieved [22]. The flexibility to increase dosing based on clinical response may contribute to the longer persistence observed with tocilizumab.…”
Section: Fig 2 Lines Of Bdmard Therapy By Biologicmentioning
confidence: 99%
“…This LTE of the phase IIIb, multinational, open-label ACT-SURE study demonstrated that the safety, tolerability, and effectiveness of TCZ administered intravenously in patients with moderate to severe RA were maintained with long-term exposure (median exposure of 64.3 weeks) in patients who had responded to TCZ after the 24-week core study. Previous clinical trials have shown the long-term efficacy and safety of TCZ [18,[21][22][23][24]27]; however, the patient population of the ACT-SURE LTE study was more representative of the broader range of patients with RA seen in clinical practice, given the minimal restrictions on concomitant medications and previous csDMARD and TNFi use and the lack of specific minimum criteria related to specific disease activity components in contrast to what is usually required in most phase III trials in RA. Thus, the ACT-SURE LTE adds to the growing body of evidence supporting the long-term effectiveness and safety of TCZ in a patient population similar to that seen in rheumatology practices.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab (TCZ), a humanized monoclonal antibody that blocks the interleukin (IL)-6 receptor-alpha, has been shown to be a safe and effective treatment for patients with early or established RA in randomized controlled trials, either as monotherapy or in combination with csDMARDs [10][11][12][13][14][15][16][17][18][19][20]. The long-term effectiveness and safety of TCZ have been established in multiple clinical trials [21][22][23][24], thus informing patient care decisions in clinical practice because patients with RA often receive prolonged treatment. However, these trials excluded patients with certain prior therapies; patients who have failed multiple therapies may have more severe disease and be at risk for more comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…in terms of treatment duration and convenience [11,12]. Examples of therapeutic proteins which have originally been formulated for IV administration and were subsequently developed for SC administration include abatacept (Orencia ® , Bristol-Myers Squibb), alemtuzumab (Lemtrada ® , Sanofi Genzyme), rituximab (MabThera ® , F. Hoffmann-La Roche), [13][14][15].…”
Section: Introductionmentioning
confidence: 99%